Oxidative Cysteine Post Translational Modifications Drive the Redox Code Underlying Neurodegeneration and Amyotrophic Lateral Sclerosis - Anna Percio; Michela Cicchinelli; Domiziana Masci; Mariagrazia Summo; Andrea Urbani; Viviana Greco (MDPI AG, 2024)
Redox dysregulation, an imbalance between oxidants and antioxidants, is crucial in the pathogenesis of various neurodegenerative diseases. Within this context, the "redoxome" encompasses the network of redox molecules collaborating to maintain cellular redox balance and signaling. Among these, cysteine-sensitive proteins are fundamental for this homeostasis. Due to their reactive thiol groups, cysteine (Cys) residues are particularly susceptible to oxidative post-translational modifications (PTMs) induced by free radicals (reactive oxygen, nitrogen, and sulfur species) which profoundly affect protein functions. Cys-PTMs, forming what is referred to as "cysteinet" in the redox proteome, are essential for redox signaling in both physiological and pathological conditions, including neurodegeneration. Such modifications significantly influence protein misfolding and aggregation, key hallmarks of neurodegenerative diseases such as Alzheimer's, Parkinson's, and notably, amyotrophic lateral sclerosis (ALS). This review aims to explore the complex landscape of cysteine PTMs in the cellular redox environment, elucidating their impact on neurodegeneration at protein level. By investigating specific cysteine-sensitive proteins and the regulatory networks involved, particular emphasis is placed on the link between redox dysregulation and ALS, highlighting this pathology as a prime example of a neurodegenerative disease wherein such redox dysregulation is a distinct hallmark.